Pengaruh Perputaran Kas Dan Perputaran Persediaan Terhadap Profitabilitas Pada PT. Indofood Sukses Makmur Tbk - Siti Zahara; Riandani Rezki Prana (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this study is to see whether there was an effect of cash turnover andinventory turnover on profitability (ROA) at PT. Indofood Sukses Makmur Tbk which is listedon the Indonesia Stock Exchange. The sample data population in this study is the financialstatements of the company PT. Indofood Sukses makmur Tbk from 2010 to 2019. The data usedwas secondary data. The analysis technique used multiple linear regression test. Based on theresearch results, it showed that cash turnover and inventory turnover simultaneously have apositive and significant effect on profitability (ROA). Partially cash turnover has no positiveand significant effect on profitability (ROA) and inventory turnover has a positive andsignificant effect on profitability (ROA).